Memantine inhibits cortical spreading depolarization and improves neurovascular function following repetitive traumatic brain injury - MacLean, Mark A.; Muradov, Jamil H.; Greene, Ryan; Van Hameren, Gerben; Clarke, David B.; Dreier, Jens P.; Okonkwo, David O.; Friedman, Alon (Science advances, 2023)
Cortical spreading depolarization (CSD) is a promising target for neuroprotective therapy in traumatic brain injury (TBI). We explored the effect of NMDA receptor antagonism on electrically triggered CSDs in healthy and brain-injured animals. Rats received either one moderate or four daily repetitive mild closed head impacts (rmTBI). Ninety-three animals underwent craniectomy with electrocorticographic (ECoG) and local blood flow monitoring. In brain-injured animals, ketamine or memantine inhibited CSDs in 44 to 88% and 50 to 67% of cases, respectively. Near-DC/AC-ECoG amplitude was reduced by 44 to 75% and 52 to 67%, and duration by 39 to 87% and 61 to 78%, respectively. Daily memantine significantly reduced spreading depression and oligemia following CSD. Animals ( N = 31) were randomized to either memantine (10 mg/kg) or saline with daily neurobehavioral testing. Memantine-treated animals had higher neurological scores. We demonstrate that memantine improved neurovascular function following CSD in sham and brain-injured animals. Memantine also prevented neurological decline in a blinded, preclinical randomized rmTBI trial. Memantine inhibited cortical spreading depolarization and prevented neurobehavioral decline following traumatic brain injury.